Midline submuscular penile prosthesis reservoir placement for patients with bilateral inaccessible inguinal rings: technique and outcomes. (December 2022) - Zisman, Ariel; Razdan, Shirin; Siegal, Alexandra; Sljivich, Michaela; Bieber, Christine; Ho, Patrick; Valenzuela, Robert
Introduction: One of the most challenging aspects of inflatable penile prosthesis (IPP) surgery is reservoir placement. The traditional space of Retzius (SOR) is not suitable for all patients. For example, radical cystectomy or prostatectomy may alter the anatomical SOR. Hence, traditional placement of the reservoir in this space increases the risk of bowel or vascular injury. Also, patients with bilateral inguinal hernias repaired with mesh, or those with previous reservoirs that have been retained, are not eligible for a Retzius reservoir. Our study reports on the use of midline sub-rectus muscle placement of a penile prosthesis reservoir in these patients as an alternative to high submuscular placement commonly used. Methods: A retrospective chart review of male patients who underwent IPP surgery between June 2017 and 2021 was conducted. Patients were divided into two groups based on the location of the reservoir: SOR versus Midline Submuscular Reservoir (MSMR). Complication rates were compared, including herniated reservoirs, infections, bowel injuries, and vascular injuries. Results: Our cohort included 461 patients who underwent IPP surgery between June 2017 and 2021 in one tertiary center. SOR was used in 89% of patients and MSMR in 11% of patients ( n  = 413 and 48, respectively). Median follow-up for all patients was 28 months. The mean age was 67 ± 8 years. There was no statistically significant difference between the two groups regarding age or comorbidities (BMI, diabetes mellitus, hypertension, hyperlipidemia, and coronary artery disease). The complication rate was low in both the SOR and MSMR groups, with device malfunction being the most common (2% versus 4%, respectively; p  = 0.32). The infection rate was 0.5% in the SOR group with no infections in the MSMR group (NS). There was only one case of herniation requiring surgical revision in the SOR group and no cases of bowel or vascular injury. Conclusion: Placement of a penile prosthesis reservoir within a midline rectus submuscular space is a safe and effective technique when the SOR is compromised by previous surgery or bilateral inguinal canals are not accessible.